DEVELOPMENT OF SOCIAL SKILL SCALE FOR EARLY CHILDHOOD - Budyartati, Sri (Premiere Educandum, 2015)
Many social skills may be learned implicitly, all children can benefit from being taught social skills explicitly, not only children who are developmentallylagging behind their peers. Social skills are not always learned easily. Somechildren may require repeated instruction and reinforcement of learning. It is alsopossible for children to have well-developed social skills in one area but not inanother. The primary objective of the Social Skill Scale (SSS) is to describe thechilds behavior for purposes of socialization and education, rather thandiagnosis. It focuses on the childs adaptation to and functioning within his or herenvironment which is particularly relevant to teachers. The SSS helps teachersdesign classroom interventions that address both the childs strengths andweaknesses. It includes 115 items that can be completed in just 15 minutes byEarly Childhood, a preschool, or Kindergarten teacher. These items cover Threebasic scales and ten components or summary scalesKeywords: Development, Social Skill Scale